Global burden and incidence trends of zika virus infection among women aged 15-49 years from 2011 to 2021: A systematic analysis - Chenyuan Qin; Yaping Wang; Min Liu; Jue Liu (Elsevier, 2024)
Background: Zika virus (ZIKV) infection during pregnancy presents a significant health risk in women of reproductive age and their offspring due to severe neurological complications. It is meaningful to assess its global burden and temporal trends. Methods: This study extracted annual incidence cases and rates of ZIKV among women of reproductive age (15-49 years) between 2011 and 2021 from Global Burden of Diseases (GBD) 2021, including global level, 21 GBD regions, 5 socio-demographic index (SDI) regions, 7 age groups, and 204 countries and territories. Relative percent change in cases and estimated annual percentage change (EAPC) of incidence rates were used to quantify the temporal trends. Results: The incidence rate of ZIKV infection exhibited a pronounced peak in 2016 at 174.27 per 100,000 population, with an EAPC of 158.30 % from 2011 to 2016 and −51.86 % from 2016 to 2021 at 3.06 per 100,000 population. And only 5 out of the 21 GBD regions reported ZIKV infection in 2021, predominantly concentrated in Latin America and Caribbean. The outbreaks were primarily concentrated in low-middle and middle SDI regions. In 2021, at the global level, the incidence rates of ZIKV infection among women of reproductive age were similar across different age groups, ranging from 2.41 to 3.39 per 100,000 population. The proportion of ZIKV infection cases was slightly higher in women aged 25-29 and 30-34 years compared to other age groups in 2021, whereas a higher proportion of cases were observed in younger age groups in 2011 and 2016. Conclusions: Women of reproductive age in Latin America and Caribbean continue to face the threat of ZIKV. Regions with lower SDI had a disproportionately severe burden. Future public health strategies should focus on high-risk areas and populations of reproductive age, enhancing surveillance, prevention, and education efforts to further mitigate the public health threat posed by ZIKV.